(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Training students of medical specialties in the use of information systems in their professional activities will be effective if the content of training in the field of information systems is brought into line with the needs of their use in certain types of professional activities of doctors.